If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 45 = 180 Reorder the terms: 45 + 11x = 180 Solving 45 + 11x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + 11x = 180 + -45 Combine like terms: 45 + -45 = 0 0 + 11x = 180 + -45 11x = 180 + -45 Combine like terms: 180 + -45 = 135 11x = 135 Divide each side by '11'. x = 12.27272727 Simplifying x = 12.27272727
| -8=-20+2.3x | | (-7x-5y)+(3x+5y)= | | 5x+6=8x+3 | | 125m-75m+48000=50500-200m | | 49x^4-9x^2=0 | | h+15h= | | 5x-20+90=180 | | -(11-3a)=-5(1-a) | | 6x+168=3x+138 | | x^2-6=-5x | | 17h-47+6h=163 | | 3x-2+5x-20=90 | | 3x-2=-2+6 | | 3x-2+90+5x-20=180 | | -3c+6d=-15 | | 10+12r+5r= | | 3x-2+5x-20=180 | | -5=2a-7 | | -2(t+4.6)=9.5 | | 125m-75m=50500-200m | | 7j(j+2)+3j(j+2)= | | 7x-8=104 | | -7z-56=-10 | | (5+6i)(2-3i)=0 | | 2b*b=x | | 2z+7=17 | | 10x-y=-1 | | 4x^2-396=4 | | 45+x=180 | | -4(-6+k)=-36 | | 8x-18=36 | | 3t+5+2t=2+4t |